‘Taser, Taser’! Exploring factors associated with police use of Taser in England and Wales - Dymond, Abi (Policing and society, 2020)
Police use of Taser in England and Wales has received little academic attention, despite being the topic of much public controversy. Much of our knowledge comes from the United States of America, but these findings are based on a small number of data sets and little testing has been done to see whether such findings apply internationally. This article uses a novel dataset from a police agency in England and Wales, and pilots new covariates, to conduct a multivariate analysis of factors associated with Taser use: the first time such analysis has been conducted outside of North America. This analysis also provides an ideal opportunity to test long-standing theoretical debates about whether police use of force is affected by ‘who the citizen is’, as the conflict approach would predict, or ‘what the citizen does’, in keeping with the consensus tradition. Variables from both the former (namely gender and mental health issues) and the latter category (including presence or use of a weapon) were found to be statistically significant after the inclusion of controls. The results highlight limitations to the application of the American based literature internationally and demonstrate stronger support for consensus than conflict theories. They also highlight that, under certain conditions, it may be appropriate for officers to take civilian characteristics into account when making use of force decisions.